Does Right-Hemispheric Anodal tDCS Enhance the Impact of Script Training in Chronic Aphasia? A Single-Subject Experimental Study - Figeys, Mathieu; Kim, Esther Sung; Hopper, Tammy (Frontiers in Rehabilitation Sciences, 2022)
Background: Script training is an aphasia treatment approach that has been demonstrated to have a positive effect on communication of individuals with aphasia; however, it is time intensive as a therapeutic modality. To augment therapy-induced neuroplasticity, transcranial direct current stimulation (tDCS) may be implemented. tDCS has been paired with other speech-language treatments, however, has not been investigated with script training. Aims: The purpose of this study was to determine if tDCS improves communication proficiency when paired with script training, compared to script training alone. Methods & Procedures: A single-subject experimental design was implemented with a participant with non-fluent aphasia, using two scripts across treatment conditions: script training with sham-tDCS, and script training with anodal-tDCS. Treatment sessions were 75 minutes long, administered three times weekly. Anodal tDCS was implemented for 20 minutes with a current of 1.5 mA over the right inferior frontal gyrus. Results: Large effect sizes were obtained on script mastery for both stimulation conditions (anodal d2 = 9.94; sham d2 = 11.93). tDCS did not improve script accuracy, however, there was a significant improvement in the rate of change of script pace relative to baseline (3.99 seconds/day, p < .001) in the anodal tDCS condition. Conclusion: Despite a null tDCS result on accuracy, the script training protocol increased script performance to a near-fluent level of communication. There is preliminary evidence to suggest that tDCS may alter the rate of script acquisition, however, further research to corroborate this finding is required. Implications for future studies are discussed.